2017
DOI: 10.1016/j.jbmt.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and physical therapy help restore body and self in clients with severe anorexia nervosa

Abstract: This file was downloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Kolnes, L.-J. (2017

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 91 publications
3
21
0
Order By: Relevance
“… 52 With regard to nausea/vomiting and loss of appetite, it could not be concluded whether exercise suppressed or promoted these symptoms. Exercise has been reported to promote nausea/vomiting 53 and could promote loss of appetite 54 in healthy people. In contrast, exercise could also suppress these symptoms in noncancer patients.…”
Section: Discussionmentioning
confidence: 99%
“… 52 With regard to nausea/vomiting and loss of appetite, it could not be concluded whether exercise suppressed or promoted these symptoms. Exercise has been reported to promote nausea/vomiting 53 and could promote loss of appetite 54 in healthy people. In contrast, exercise could also suppress these symptoms in noncancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…NPMP is described in more detail elsewhere 32. The method differs from traditional physiotherapy in that it understands the body to be a functionally integrated entity, such that (1) constriction in one part of the body influences the steadiness of the entire body and (2) that lived experiences and feelings are embedded within the body 32 40. The assessment of the breathing pattern is of particular interest, as it is assumed that emotional or physical stress over time may constrict the breathing and cause tension in bodily function and movements 30.…”
Section: Methodsmentioning
confidence: 99%
“…A pattern of upper chest breathing accompanied by increased muscle tension in respiratory muscles, possibly triggered by increased parasympathetic activity as previously shown in endurance athletes (Filipe, Falcao-Reis, Castro-Correia, & Barros, 2003;Kaltsatou, Kouidi, Fotiou, & Deligiannis, 2011), is frequently seen in young elite athletes with EILO receiving physical therapy for their breathing difficulties (Kolnes, 2016b). If upper chest breathing becomes the habitual breathing pattern, compensatory changes such as increased activation of respiratory muscles, absence of diaphragmatic descent and postural de-alignments characterized by a forward head posture and increased extension of the lower cervical spine are likely to emerge (Kapreli, Vourazanis, & Strimpakos, 2008;Kolnes, 2016a;Perri & Halford, 2004). Eventually, proprioception and neuromuscular control of the muscles of the neck become disrupted and the neuromuscular coordination of cervical movements during respiration is impaired, subsequently affecting the position of the larynx and laryngeal movements.…”
Section: Discussionmentioning
confidence: 99%
“…Such a standing position requires modest muscular effort and allows for spontaneous changes in posture and breathing pattern. Clinical experiences have demonstrated that the breathing typically become less restrained and more diaphragmatic as the person´s posture alters from being rigid and inflexible to becoming more balanced and flexible (Kolnes, 2016a).…”
Section: Discussionmentioning
confidence: 99%